2001
DOI: 10.1557/jmr.2001.0356
|View full text |Cite
|
Sign up to set email alerts
|

18O study of the oxidation of reactively sputtered Ti1−xAlxN barrier

Abstract: The preparation of high-permittivity perovskite materials requires high-temperature (550–750 °C) oxidizing environments, providing stringent limitations on the choice of electrode materials. To minimize interdiffusion and oxidation reactions, an electrically conductive diffusion barrier such as Ti1−xAlxN is needed below the electrode material (Pt, IrO2, RuO2…). Ti1−xAlxN films were deposited by multitarget reactive sputtering in a mixture of Ar and N2. The stability of these films has been investigated under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Due to the extremely limited kinetics (condensation from the vapor phase can be assigned with cooling rates up to 10 13 K s À1 (104)) apparent in PVD deposition techniques it is possible to synthesize a supersaturated solid solution of Ti 1Àx Al x N (10,11,(105)(106)(107)(108)(109), although c-TiN and w-AlN exhibit essentially no solubility for each other; see the schematic quasibinary phase diagram in Figure 7(a) (110). Ti 1Àx Al x N can be regarded as a model system in materials science of thin films, as it was shown that hardness, oxidation resistance, and thus thermal stability increases with the Al content, x, within the cubic regime (24,79,80,103,111,(114)(115)(116)(117)(118)(119). In the region where E f exhibits almost similar values for cubic and wurtzite structures, a dual phase regime is preferred, followed by a single-phase wurtzite regime for higher Al contents (79,81,98,111,112).…”
Section: Al-containing Transition Metal Nitridesmentioning
confidence: 99%
“…Due to the extremely limited kinetics (condensation from the vapor phase can be assigned with cooling rates up to 10 13 K s À1 (104)) apparent in PVD deposition techniques it is possible to synthesize a supersaturated solid solution of Ti 1Àx Al x N (10,11,(105)(106)(107)(108)(109), although c-TiN and w-AlN exhibit essentially no solubility for each other; see the schematic quasibinary phase diagram in Figure 7(a) (110). Ti 1Àx Al x N can be regarded as a model system in materials science of thin films, as it was shown that hardness, oxidation resistance, and thus thermal stability increases with the Al content, x, within the cubic regime (24,79,80,103,111,(114)(115)(116)(117)(118)(119). In the region where E f exhibits almost similar values for cubic and wurtzite structures, a dual phase regime is preferred, followed by a single-phase wurtzite regime for higher Al contents (79,81,98,111,112).…”
Section: Al-containing Transition Metal Nitridesmentioning
confidence: 99%
“…It is reported that the thickness of the oxide layer grown on the film surface decreases with increasing Al content in the films. The fine aluminum oxide on the surface of films prevented films from further oxidation [7]. The SIMS oxygen depth profile and the GAXRD patterns in Fig.…”
Section: Methodsmentioning
confidence: 99%